Homology-independent targeted insertion-mediated derivation of M1-biased macrophages harbouring Megf10 and CD3ζ from human pluripotent stem cellsResearch in context - Xing Zhen; Jieun Kim; Jong Soon Kang; Byeong Jo Choi; Ki Hwan Park; Dong-Seok Lee; Seok-Ho Hong; Jong-Hee Lee (EBioMedicine)
Summary: Background: Macrophages engineered with chimeric antigen receptors (CAR) are suitable for immunotherapy based on their immunomodulatory activity and ability to infiltrate solid tumours. However, the production and application of genetically edited, highly effective, and mass-produced CAR-modified macrophages (CAR-Ms) are challenging. Methods: Here, we used homology-independent targeted insertion (HITI) for site-directed CAR integration into the safe-harbour region of human pluripotent stem cells (hPSCs). This approach, together with a simple differentiation protocol, produced stable and highly effective CAR-Ms without heterogeneity. Findings: These engineered cells phagocytosed cancer cells, leading to significant inhibition of cancer-cell proliferation in vitro and in vivo. Furthermore, the engineered CARs, which incorporated a combination of CD3ζ and Megf10 (referred to as FRP5Mζ), markedly enhanced the antitumour effect of CAR-Ms by promoting M1, but not M2, polarisation. FRP5Mζ promoted M1 polarisation via nuclear factor kappa B (NF-κB), ERK, and STAT1 signalling, and concurrently inhibited STAT3 signalling even under M2 conditions. These features of CAR-Ms modulated the tumour microenvironment by activating inflammatory signalling, inducing M1 polarisation of bystander non-CAR macrophages, and enhancing the infiltration of T cells in cancer spheroids. Interpretation: Our findings suggest that CAR-Ms have promise as immunotherapeutics. In conclusion, the guided insertion of CAR containing CD3ζ and Megf10 domains is an effective strategy for the immunotherapy of solid tumours. Funding: This work was supported by KRIBB Research Initiative Program Grant (KGM4562431, KGM5282423) and a Korean Fund for Regenerative Medicine (KFRM) grant funded by the Korean government (Ministry of Science and ICT, Ministry of Health and Welfare) (22A0304L1-01).